Internal Consistency of Academic Scores as an Index of the Validity of Course Exams: a study in Faculty of Pharmacy Kerman University of Medical Sciences - Ashraf Adhami; Ali Akbar Haghdoost; Ali Akbar Haghdoost; Payam Khazaeli; Marhamat Afzali (Kerman University of Medical Sciences, 2012)
Background & Objectives: In order to improve the quality of teaching attention to the students academic progress is important In the present study the internal consistency of students scores has been used as an index for the evaluation of the validity of course exams Methods: All scores of Pharmacy students graduated in 2007 and 2008 were collected from the of Kerman University of Medical Sciences We computed the Pearson correlation coefficient (r) between course scores and grade point average (GPA) In addition coefficients between the mean score in subgroups of courses with GPA were computed Results : In most courses the correlation coefficient between the course score and GPA was in the range of 04 to 06 The lowest correlation coefficients belonged to sport course (004) and thesis (033) while the highest were for theoretical biochemistry (078) and practical chemistry (076) The correlation coefficient of male students scores was 049 and that of female students was 040 that shows significant difference (p < 001) In whole the scores of basic courses showed higher correlation compared to general and special courses The correlations in theoretical and practical courses were equal Conclusion: It seems that this convenient method for investigating the internal consistency of course scores can be used as an index for validity of corse scores Significant difference in correlation coefficients among different courses requires special attention to some courses for investigating the probable testing errors even though in most courses the coefficients were in the acceptable range